Analysis of The Influence of The Size of KAP, Management Turnover and Size of Company toward Auditor Switching (An Empirical Study on Manufacturing Companies Registered in Indonesian Stock Exchange Year 2011-2015) - Nurcahyo, Dhanar Dwika; Anisykurlillah, Indah (Accounting Analysis Journal, 2017)
Auditor Switching merupakan proses pergantian KAP yang dilakukan oleh perusahaan. Pergantian KAP di Indonesia dapat dilakukan secara mandatory ataupun voluntary. Pergantian KAP secara voluntary dapat menimbulkan kecurigaan dari stakeholder untuk mengetahui apa yang penyebabnya. Populasi dalam penelitian ini adalah perusahaan manufaktur yang terdiri dari 170 perusahaan. Teknik purposive sampling menghasilkan sampel sebanyak 29 perusahaan. Variabel independen dalam penelitian ini adalah Ukuran KAP, Pergantian Manajemen, dan Ukuran Perusahaan. Variabel dependen dalam penelitian ini adalah Auditor Switching. Hasil penelitian ini menunjukkan bahwa variabel Ukuran KAP berpengaruh negatif terhadap auditor switching, variabel Ukuran Perusahaan berpengaruh negatif terhadap auditor switching. Sementara variabel Pergantian Manajemen tidak berpengaruh terhadap auditor switching. Saran untuk Penelitian selanjutnya mengenai Auditor Switching, diharapkan dapat menerapkan Perturan Menteri Keuangan yang terbaru tahun 2015 yaitu Peraturan Menteri Keuangan Republik Indonesia Nomor 20 tahun 2015. Pergantian manajemen untuk penelitian selanjutnya disarankan untuk melihat dari pergantian Dewan Komisaris, Karena Dewan Komisaris dalam perusahaan memiliki andil dalam pemilihan Kantor Akuntan Publik. Auditor Switching is  an exchanging of KAP  which is conducted by the company.  The change of KAP in Indonesia can be conducted by mandatory and voluntary. Auditor Switching by voluntary may raise suspicion of stakeholders to find out what the cause. The purpose of this study is to analyze the influence of Size of KAP, Management Turnover, and Size of Company toward Auditor Switching. The population in this study are the manufacturing companies which consist of 130 companies. The technique of purposive sampling which results for 57 samples. The independent variables in this study are management turnover, size of KAP, and size of comoany. While the dependent variable in this study is Auditor Switching. The results of this study shows that the following variable size of KAP have a negative affect toward auditor switching, but management turnover and size of company donât have an affect toward auditor swithing. The value of Nagelkerke R Square is 0.192, itâs mean that the variation of the dependent variable that can be explained by the independent variable arround 19.2%, and the remaining 80.8% is explained by other variables outside the model. For the next research on auditor switching is expected to apply the newest Ministry of Finance Regulation in 2015, namely the Indonesian Government Numer 20 year 2015.